“Proyecto de Inversión para la Producción y Comercialización de Crema de Licor a base de Luma en la Ciudad de Loja” - Sarango Gálvez, Diego Fernando (2025)
The purpose of this study called “Investment project for the production and commercialization of cream liqueur based on luma in Loja city” was to determine the financial feasibility of its implementation, for this purpose a representative sample of the Economically Active Population (EAP) in Loja city was calculated to determine the approval of the product using market, technical and financial studies to obtain a complete picture. A mixed qualitative and quantitative approach was applied, which allowed us to know the tastes and preferences of consumers and other variables related to consumption. The market study determined that there is an unsatisfied demand of 274,038 bottles of cream liqueur. The technical study determined the installed capacity of 197,100, a capacity utilization of 4320 bottles per year, thus achieving a 6.94% market share for the first year, the organizational structure of the company includes a manager, secretary, worker and salesperson/distributor. The financial indicators such as the net present value (NPV) is estimated at $ 26,392.10, followed by the internal rate of return (IRR), which was estimated at 63%, and the benefit-cost ratio (BCR), which was calculated at $1.26. Finally, the capital recovery period (CRP) was estimated at 1 year, 4 months and 24 days from the execution of the project. A sensitivity analysis is elaborated determined by two factors, the increase in costs in which the project can tolerate an increase of 6.70%, obtaining a 0.99 close to one, likewise with the decreased income obtaining that a decrease of up to 5.20% is tolerated, obtaining a 0.98 determining that the project is not sensitive and can be executed.